MOLECULAR DYNAMICS SIMULATIONS OF SEVERAL SELECTED COMPOUNDS FROM THE HERBAL DATABASE OF INDONESIA RESULTS OF MOLECULAR DOCKING AGAINST DNA METHYLTRANSFERASE ENZYME - Ihsan, Muhamad Fikri; Yanuar, Arry (International Journal of Applied Pharmaceutics, 2018)
Objective: This study aimed to investigate the interactions of DNA methyltransferase (DNMT) enzymes and potential ligands as DNMT inhibitors through molecular dynamics simulations. Methods: This study was conducted using tools in the form of hardware (primary and secondary computers) and software (OpenBabel, AutoDock Tools, Amber MD, Amber Tools, VMD, PuTTY, LigandScout, and UCSF Chimera). Results: Results of molecular docking of cassiamin C, procyanidin B2, epicatechin-4alphaent-8-ent-epicatechin, epicatechin-4beta-8-epicatechin- 3-O-gallate, neorhusflavanone, 3-O-galloylepigallocatechin -4beta-6-epicatechin-3-O-gallate, withanolide, 3-O-galloylepigallocatechin-4beta-6- epigallocatechin-3-O-gallate, cyanidin-3-6″-caffeylsophoroside-5-glucoside, epifriedelinol, gallocatechin-4alpha-8-epicatechin, scutellarein-7- glucosyl-1-4-rhamnoside, epigallocatechin-3-gallate (EGCG) (positive control), and sinefungin (co-crystal) compounds showed ΔG values −9.34, −10.95, −7.95, −11.01, −8.78, −8.87, −11.49, −7.98, −5.92, −8.92, −9.17, −8.76, −9.70, and −9.11 kcal/mol, respectively. Cassiamin C, procyanidin B2, epicatechin-4-beta-8-epicatechin-3-O-gallate, withanolide, and gallocatechin-4alpha-8-epicatechin compounds had lower ΔG than sinefungin (cocrystal) and EGCG (positive control) compounds. The results of molecular dynamic simulation of seven selected compounds showed the best overall activities were procyanidin B2, epicatechin-4beta-8-epicatechin-3-O-gallate, and gallocatechin-4alpha-8-epi-catechin compounds. Conclusions: The best overall activities based on molecular docking and molecular dynamic simulation were procyanidin B2, epicatechin-4beta- 8-epicatechin-3-O-gallate, and gallocatechin-4alpha-8-epi-catechin compounds. Amino acid residues that are important for the activity of DNMT1 inhibitor are Phe1145, Glu1168, Met1169, Cys1191, Glu1266, Ala1579, and Val1580.